ANALISA PERTUMBUHAN DAN PRODUKSI BENIH KACANG KORO PEDANG (Canavalia ensiformis L) MELALUI APLIKASI PUPUK NPK DAN PUPUK ORGANIK CAIR - Sarijan, Abdullah -; Surahman, M.; Setiawan, A.; Giyanto, Giyanto (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2019)
The research was aimed to enhance growth and seed production of Jack Bean by NPK and organic liquid fertilizer. The research was carried out from May to October 2016 in Purwasari village, Dramaga, Bogor and be continued by seed testing (Desember 2016) at Seed Testing Laboratory, Bogor Agricultural Institute. The research was arranged in Randomized Block Design 2 factors. The first factor is NPK fertilizer (Urea, SP-36, KCl), consists of 3 levels (0 kg ha-1as control, 25: 50: 56.25 kg ha-1, and 50: 100: 112.5 kg ha-1). The second factor is liquid organic fertilizer, consist of 2 levels (0 ml per liter of water and 2 ml per liter of water). There was no interaction between NPK and liquid organic fertilizer for the growth, production, and quality of seeds. The singly NPK and liquid organic fertilizer effected several variables. The highest seed production 4.17 tons ha-1. The 1000 grain weight produced is classified as medium to large sized seeds (> 1000 g 1000 seeds-1) and has a percentage of germination above eighty-five percent.